Analysis of Inland Wetland using Advance Remote Sensing and GIS on IRS P6 February 2005 Data of Bhopal (M.P.) - Sourabh Shrivastava (Institute of Advanced Engineering and Science, 2012)
Wetlands are the transitional zones between permanently aquatic and dry terrestrial ecosystems. Wetland systems directly and indirectly support millions of people, providing goods and services to them. The use of remote sensing technology for the mapping, identification, inventory and classification of the wetlands has been a common application of satellite imagery. Remote sensing has provided a great mean to study various ecosystems of the earth including wetlands by providing cost and time effective data. For a country like India, with its vast biological and cultural diversity, a comprehensive use of remote sensing, GIS and other related technologies is of great use in their conservation.DOI: http://dx.doi.org/10.11591/ij-ict.v1i1.547